Coral Lírico de Minas Gerais e a prática musical como política pública: patrimônio, tradição e modernidade - André Luis Felipe (2020)
Having as axle the musical ethnography of the commemorative events of the 40 years of the Lyric Choir of Minas Gerais and the concession to the group of the title of state's cultural and historic patrimony, this work considers an inquiry of the professional musical practice in question, from the slight knowledge of evidenced tradition and patrimony in official discourse in the related events. From the perspective of historical and sociological studies that contextualize the theme, we sought to extract meanings from this musical making - based on public policy - in a metropolis that was born to be a showcase of Brazilian modernity. The events also made visible the different ways through which groups within the Lyric Choir appropriated the official discourse as empowerment and resistance strategies, revealing the struggle for the maintenance of a “modern tradition” that guaranteed for the lyric singing a place in the diversified field artistic-musical of the capital of Minas Gerais.